Ecotourism Cluster and Prospects for The Sangzor-Jizzakh Reservoir: Klaster Ekowisata dan Prospek Waduk Sangzor-Jizzakh - Shukurboeva, Sanaeva Lola; Safarovich, Safarov Karimjon (Academia Open, 2024)
One of the ecotourism clusters in the Jizzakh region is the Sangzar-Molguzar ecotourism cluster, the creation of which is the basis for the systematic and sustainable development of ecotourism in the region, as well as the formation of local infrastructure. Highlights: Sangzar-Molguzar Cluster: Foundation for Jizzakh’s ecotourism development. Ecotourism Goal: Systematic, sustainable growth in regional tourism initiatives. Local Infrastructure: Cluster drives infrastructure formation in the area. Keywords: Ecotourism, cluster, ecology, Koytash, stones of various shapes, eco-routes, investments, benefits, ecotourism areas, Forish district.